The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1177/147323000303100208
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Mandibular Nutrient Canals and Hypertension

Abstract: This study was undertaken to investigate the correlation between the presence of nutrient canals in the mandibular anterior region and hypertension. Periapical radiographs taken from the mandibular anterior region of 139 normotensive and 76 hypertensive edentulous patients were examined. There was no statistical difference in the incidence of nutrient canals between normotensive and hypertensive patients, suggesting that the presence of nutrient canals is not indicative of the existence of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…The p-value was found to be 0.672 which was statistically insignificant. The results of the study are in accordance with the studies done by Yilmaz et al [14] who stated that there was no statistical difference in the incidence of nutrient canals between normotensive and hypertensive patients. The studies by Jaju et al [11] also had similar findings which stated that the incidence of nutrient canals was almost the same in hypertensive and the normal group.…”
Section: Group II (Hypertension) and Nutrient Canalssupporting
confidence: 94%
“…The p-value was found to be 0.672 which was statistically insignificant. The results of the study are in accordance with the studies done by Yilmaz et al [14] who stated that there was no statistical difference in the incidence of nutrient canals between normotensive and hypertensive patients. The studies by Jaju et al [11] also had similar findings which stated that the incidence of nutrient canals was almost the same in hypertensive and the normal group.…”
Section: Group II (Hypertension) and Nutrient Canalssupporting
confidence: 94%
“…[10], 75% in Yilmaz et al . [21] studies, 70.4%–78% of hypertensive patients depending edentulous or dentulous condition by Patni et al . [8] studies.…”
Section: Discussionmentioning
confidence: 99%
“…[10], and Yilmaz et al . [21] previous studies. The reason for this may be attributed to the principal effects of HT that is dilatation of arterioles, hypertrophy, and hyperplasia of the arterial walls and atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed the higher incidence of nutrient canals in the study group (55.2%) when compared to control group (36.2%) which was in accordance to the two previous studies reported. [3589] The principal effects of hypertension are dilatation of arterioles, hypertrophy, and hyperplasia of the vessel wall and arteriosclerosis. In arteriosclerosis, along with thickening of the arterial wall, there is narrowing of the lumen, which may lead to the opening of more collateral, or both of these changes may be responsible for the increased incidence of nutrient canals in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%